2020
DOI: 10.1186/s12864-020-6450-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis indicates conversion of stamens into pistil-like structures in male sterile wheat (Triticum aestivum L.) with Aegilops crassa cytoplasm

Abstract: Background: Aegilops crassa cytoplasm is an important source for investigating cytoplasmic male sterility (CMS). Moreover, the stamens of line C303A exhibit a high degree of pistillody, turning almost white. However, the molecular mechanism that underlies pistillody in C303A remains unclear. Therefore, to obtain a better understanding of pistillody in C303A, the phenotypic and cytological features of C303A were observed to identify the key stage for the homeotic transformation of stamens into pistil-like struc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…BLAST results showed that the predicted protein of TraesCS3B02G318300 is identical by 99% with TaAGL14 , 98% with TaAGL15 in wheat , and 87% with OsMADS32 in rice . Furthermore, TaAGL14 , TaAGL15, and OsMADS32 together, form a distinctive clade of MIKC -type gene family found only in grasses with no representatives from Arabidopsis [ 77 , 78 ] reported the involvement of TaAGL14 in stamen and pistils development in wheat. Here, we provide the first evidence about the function of the TaAGL14 gene in an earlier reproductive stage in floral meristem activation in wheat, which may very likely be similar to OsMADS32 function in rice.…”
Section: Discussionmentioning
confidence: 99%
“…BLAST results showed that the predicted protein of TraesCS3B02G318300 is identical by 99% with TaAGL14 , 98% with TaAGL15 in wheat , and 87% with OsMADS32 in rice . Furthermore, TaAGL14 , TaAGL15, and OsMADS32 together, form a distinctive clade of MIKC -type gene family found only in grasses with no representatives from Arabidopsis [ 77 , 78 ] reported the involvement of TaAGL14 in stamen and pistils development in wheat. Here, we provide the first evidence about the function of the TaAGL14 gene in an earlier reproductive stage in floral meristem activation in wheat, which may very likely be similar to OsMADS32 function in rice.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared with other model plants such as Arabidopsis thaliana and rice, there is little basic molecular research into S. miltiorrhiza and its genetic background is poorly established. In recent years, transcriptome sequencing using the Illumina platform has been employed as a powerful tool with a wide range of applications, such as cell-type-specific biological processes, to address fundamental problems related to biology on an evolutionary time scale ( Liu et al, 2020 ). The molecular mechanisms related to secondary metabolism, especially the synthesis of tanshinone and salvianolic acid, have been relatively well-studied in S. miltiorrhiza , while the molecular and genetic mechanisms related to morphological development are not well-studied ( Zhan et al, 2019 ; Yang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…This revolution was essential in addressing food scarcity and relieving global hunger. However, various abiotic factors, such as salt, drought, heavy metals, and severe temperatures, frequently threaten wheat production (Dradrach et al 2022, Iqbal et al 2023, Niu et al 2023). Abiotic stresses are the major agricultural limitation that limits the crop growth and productivity of many crops worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin, identified as a growth regulator in higher plants in 1995, has positive effects on regulating various biological processes (Ahmad et al 2021, Samanta et al 2021, Niu et al 2023, Dongxiao et al 2017). It significantly impacts physiology by increasing the antioxidant defense system (Dawood 2022) and boosts plant resistance to abiotic stress (Rajora et al 2022).…”
Section: Introductionmentioning
confidence: 99%